The Effect of Transformational Leadership and Work Motivation on Organizational Citizenship Behavior: Does Work Engagement Matter? - Aldita Prabandari; Asri Laksmi Riani (Sebelas Maret Business Review, 2017)
This study aims to analyze if transformational leadership and work motivation affect work engagement which in turn affect Organizational Citizenship Behavior (OCB). We also analyze whether work engagement mediates the effect of transformational leadership and work motivation on OCB. Using census method, our sample in this study is 73 civil servants in the Education Office in Surakarta Municipality. The sample taken for this study is all employees with census method, thus, resulting in 73 people as samples. From the analysis using Structural Equation Modelling (SEM), we find that transformational leadership positively and significantly affect OCB, this implies that leader’s attitude that inspires and motivates subordinate, stimulates creativity and innovation of subordinate, train and provide direction for subordinate, will improve subordinate OCB. Work motivation also has a positive and significant effect on OCB. Employee’s work motivation affects the development of employee’s job attachment to their organization. If the work motivation is higher, the OCB behavior will be stronger. Thus extra role behavior will increase. Also, we also find that transformational leadership and work motivation indirectly affect OCB through employee work engagement. The implication this study brings to Surakarta Municipality Education Office is to improve transformational leadership style because the style has been proven to be able to improve work engagement and OCB. Thus, it is necessary for the leaders in the office to be open-minded or open to changes that will benefit the organization either in system or technology. Besides that, the result also brings implication to Surakarta Municipality Education Office to consider subordinate’s work motivation